Differential Regulation of Microglial Activation in Response to Different Degree of Ischemia - Gao, Hao; Ju, Furong; Ti, Rujuan; Zhang, Yue; Zhang, Shengxiang (Frontiers in Immunology, 2022)
Microglia are primary immune cells within the brain and are rapidly activated after cerebral ischemia. The degree of microglial activation is closely associated with the severity of ischemia. However, it remains largely unclear how microglial activation is differentially regulated in response to a different degree of ischemia. In this study, we used a bilateral common carotid artery ligation (BCAL) model and induced different degrees of ischemia by varying the duration of ligation to investigate the microglial response in CX3CR1GFP/+ mice. Confocal microscopy, immunofluorescence staining, RNA sequencing, and qRT-PCR were used to evaluate the de-ramification, proliferation, and differential gene expression associated with microglial activation. Our results showed that 30 min of ischemia induced rapid de-ramification of microglia but did not have significant influence on the microglial density. In contrast, 60 min of ischemia led to a significant decrease in microglial density and more pronounced de-ramification of microglial processes. Importantly, 30 min of ischemia did not induce proliferation of microglia, but 60 min of ischemia led to a marked increase in the density of proliferative microglia. Further analysis utilized transcriptome sequencing showed that microglial activation is differentially regulated in response to different degrees of ischemia. A total of 1,097 genes were differentially regulated after 60 min of ischemia, but only 68 genes were differentially regulated after 30 min of ischemia. Pathway enrichment analysis showed that apoptosis, cell mitosis, immune receptor activity and inflammatory-related pathways were highly regulated after 60 min of ischemia compared to 30 min of ischemia. Multiple microglia-related genes such as Cxcl10, Tlr7, Cd86, Tnfrsf1a, Nfkbia, Tgfb1, Ccl2 and Il-6, were upregulated with prolonged ischemia. Pharmacological inhibition of CSF1 receptor demonstrated that CSF1R signaling pathway contributed to microglial proliferation. Together, these results suggest that the proliferation of microglia is gated by the duration of ischemia and microglia were differentially activated in responding to different degrees of ischemia.